Interaction Approach and Liabilities: A Case Analysis of Start-Up Firms. Issue 4 (1st October 2016) - Guercini, Simone; Milanesi, Matilde
ABSTRACT: Purpose : Start-up firms have to face some key challenges due to liabilities related to processes that are external to the organization, such as establishing relationships with customers, suppliers and other relevant actors. The purpose of the article is to understand how liabilities, namely newness, smallness, foreignness and outsidership, are related to each other in start-ups, and what are the main liabilities perceived/experienced by start-ups and their counterparts, using an interactive perspective. Methodology : The article uses a case study methodology and proposes 3 cases of start-ups firms and their counterparts. Cases are built using multiple data-sources, both primary and secondary. Findings : The article highlights the role of "heritage" left by the membership in the network. This "network heritage" means that some aspects of the network are pre-existing, in terms of previous and long lasting relationships with other actors. In this sense, the network in which the firm connects pre-exists and mitigates the existence of liabilities that come into play in the processes of interdependence with other actors. This provides a perspective of liabilities, specifically the liability of newness, as an asset in the sense that newness depends on a "short story, " without constraints of a "longer story" as that of competitors in the network. The liability of newness is an asset in terms of flexibility, customized offer and innovative content. Originality/value/contribution : The main contribution of the article lies in taking an interactive perspective on start-ups and liabilities, analyzing the interaction processes taking place between the new venture and the surrounding network of essential actors. Practical implications : Liabilities arise and can be overcome in the processes of interaction, which therefore can have an ambivalent role: fertile ground for the manifestation of liabilities but also the context for its overcoming/conversion of liabilities into assets. Entrepreneurs and managers should consider newness and smallness as positive attributes for other actors in the processes of interaction, as a potential generator of value. Such a perception of newness as an asset depends on two factors: the presence or absence of an organization-mother that limits the perception of newness as a liability; the sector in which the new company develops, if dynamic and innovative or still tied to traditional and consolidated processes where the experience, "history" and "heritage" of the firm are sources of legitimacy.